Clinical efficacy, safety and tolerability of collagenase clostridium histolyticum for the treatment of peyronie disease in 2 large double-blind, randomized, placebo controlled phase 3 studies - Gelbard, Martin; Goldstein, Irwin; Hellstrom, Wayne J G; McMahon, Chris G; Smith, Ted; Tursi, James; Jones, Nigel; Kaufman, Gregory J; Carson, 3rd, Culley C (The Journal of urology, 2013)
IMPRESS (Investigation for Maximal Peyronie's Reduction Efficacy and Safety Studies) I and II examined the clinical efficacy and safety of collagenase Clostridium histolyticum intralesional injections in subjects with Peyronie disease. Co-primary outcomes in these identical phase 3 randomized, double-blind, placebo controlled studies included the percent change in the penile curvature abnormality and the change in the Peyronie disease questionnaire symptom bother score from baseline to 52 weeks. IMPRESS I and II examined collagenase C. histolyticum intralesional injections in 417 and 415 subjects, respectively, through a maximum of 4 treatment cycles, each separated by 6 weeks. Men received up to 8 injections of 0.58 mg collagenase C. histolyticum, that is 2 injections per cycle separated by approximately 24 to 72 hours with the second injection of each followed 24 to 72 hours later by penile plaque modeling. Men were stratified by baseline penile curvature (30 to 60 vs 61 to 90 degrees) and randomized to collagenase C. histolyticum or placebo 2:1 in favor of the former. Post hoc meta-analysis of IMPRESS I and II data revealed that men treated with collagenase C. histolyticum showed a mean 34% improvement in penile curvature, representing a mean ± SD -17.0 ± 14.8 degree change per subject, compared with a mean 18.2% improvement in placebo treated men, representing a mean -9.3 ± 13.6 degree change per subject (p <0.0001). The mean change in Peyronie disease symptom bother score was significantly improved in treated men vs men on placebo (-2.8 ± 3.8 vs -1.8 ± 3.5, p = 0.0037). Three serious adverse events (corporeal rupture) were surgically repaired. IMPRESS I and II support the clinical efficacy and safety of collagenase C. histolyticum for the physical and psychological aspects of Peyronie disease.